STUDI PENGELOLAAN WAKAF TUNAI DI LEMBAGA AMIL ZAKAT NASIONAL BAITUL MAAL HIDAYATULLAH KENDARI - Toto Iswanto; Gamsir Gamsir; Ernawati Ernawati (JEP (Jurnal Ekonomi Pembangunan), 2019)
Based on the research that has been done that in collecting cash Waqf funds, the party of Baitul Maal Hidayatullah Kendari used several strategies gathering direct, direct and indirect, Waqf funds collected Then utilized by Baitul Maal Hidayatulah Kendari and managed still traditionally can be seen from the utilization is only used such as the procurement of Quran and Mushaf and the manufacture of Bor Wells, Baitul Maal Hidayatullah Kendari in managing Waqf cash is in accordance with Islamic sharia because it has enough terms and the pillars and as well as the implementation of the cash Waqf pledge is done in writing. By completing the Cash Waqf allocation form will be given. This allocation form is a cash Waqf certificate form that has been provided by Baitul Maal.